Problematika Kewenangan Penyelesaian Sengketa Pilkada: Antara Kepastian Hukum Dan Inkonsistensi - Sari, Winda (UI Scholars Hub, 2023)
This article examines two main issues. First, the position of regional head elections (pilkada) in the general election regime. Second, the ideal institution in handling disputes over election results. The research method used is doctrinal, with statutory and conceptual approaches. The results of the study show that the implementation of regional elections is based on the provisions of the 1945 Constitution of the Republic of Indonesia and Law Number 1 of 2015. By reason of its presence as a manifestation of popular sovereignty; periodic elections; the use of direct, general, free, confidential, honest and fair principles in practice; minutes of the Ad hoc session of the formation of Article 18 of the Constitution; and the organizer of the elections is the general election commission, the elections are part of the electoral regime. Thus, despite the inconsistency in interpreting the election regime, the Constitutional Court (MK) is the ideal institution to resolve disputes over election results. Due to two main reasons, namely the constitution mandates the examination of disputes over election results to the Constitutional Court and in terms of practice, from 2008 to 2022 the Constitutional Court can consistently decide disputes over election results.